The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1083/jcb.200203048
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-controlled competitive diacylglycerol binding of protein kinase C isoenzymes in living cells

Abstract: The cellular decoding of receptor-induced signaling is based in part on the spatiotemporal activation pattern of PKC isoforms. Because classical and novel PKC isoforms contain diacylglycerol (DAG)-binding C1 domains, they may compete for DAG binding. We reasoned that a Ca2+-induced membrane association of classical PKCs may accelerate the DAG binding and thereby prevent translocation of novel PKCs. Simultaneous imaging of fluorescent PKC fusion proteins revealed that during receptor stimulation, PKCα accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 44 publications
(47 reference statements)
2
66
1
Order By: Relevance
“…The faster generation of DAGs from phosphatidylinositol hydrolysis vs. phosphatidylcholine hydrolysis (Nishizuka, 1995) may predispose to activation of cPKCs instead of nPKCs. Evidence from other studies suggests that the more rapid kinetics of cPKC translocation is determined by the calcium transients (Oancea, 1998;Lenz et al, 2002;Gallegos et al, 2006). In summary, although phosphorylation at specific PKC sites in the I-II linker and C-terminus would seem to be sufficient for activation of Ca v 2.2 channels, in the Ca v 2.3 channels, these sites may be necessary but not sufficient.…”
Section: Discussionmentioning
confidence: 91%
“…The faster generation of DAGs from phosphatidylinositol hydrolysis vs. phosphatidylcholine hydrolysis (Nishizuka, 1995) may predispose to activation of cPKCs instead of nPKCs. Evidence from other studies suggests that the more rapid kinetics of cPKC translocation is determined by the calcium transients (Oancea, 1998;Lenz et al, 2002;Gallegos et al, 2006). In summary, although phosphorylation at specific PKC sites in the I-II linker and C-terminus would seem to be sufficient for activation of Ca v 2.2 channels, in the Ca v 2.3 channels, these sites may be necessary but not sufficient.…”
Section: Discussionmentioning
confidence: 91%
“…FRET from CFP to YFP was determined by excitation of CFP (425 nm) and measurement of fluorescence emitted from YFP (535/26 nm). The maximum FRET capability of the system was defined by determining FRET from CFP to YFP in a fusion protein consisting of the two proteins (42). Background fluorescence from a region with no cells was subtracted from the data.…”
Section: Methodsmentioning
confidence: 99%
“…Schaefer et al (31,32) suggested that differences in translocation between classical and novel PKCs are due to differences in diffusion rates, and collision efficiencies with the membrane. Although diffusion and collision with the membrane are likely factors in the translocation rate, our data demonstrate that conformational changes in the enzyme also occur, leading to at least a two-step process.…”
Section: Mathematical Modeling Of ⑀Pkc Translocation Suggests That ⑀Pmentioning
confidence: 99%